Question words and noun paradigms - Dagny Hildegard Skaile; Joshua Karl Wilbur (Joshua Wilbur, 2008)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) some question words; some noun paradigms: sábme (Saami), várre (mountain), jávvre (lake), náhppe (milking bowl)